Pengaruh Rutinitas Membaca Asmaul Husna terhadap Pembentukan Karakter Siswa di SDN 003 Balikpapan - Mochammad Dwiky Anugrah; Al Wardah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the effect of the Asmaul Husna reading routine on character building among sixth-grade students at SDN 003 Balikpapan. The study uses a quantitative approach with a correlational research design. The research subjects include all 89 sixth-grade students, with a saturated sampling technique used for sample selection. Data were collected through a Likert scale questionnaire, observation, and documentation, then analyzed using simple linear regression with the help of SPSS version 25. The results showed that the routine of reading Asmaul Husna had a strong relationship with the character building of students, as indicated by a correlation coefficient value of 0.647. The coefficient of determination value of 0.419 indicates that the routine of reading Asmaul Husna contributes 41.9% to the formation of student character. The ANOVA test produced a significance value of 0.000, indicating that the regression model is statistically significant. These findings show that the habit of consistently reading Asmaul Husna plays an important role in instilling religious values, discipline, and positive attitudes in students in the elementary school environment.